Living Qur’an dan Hadis di MI Nurul Ummah (Rutinitas, Ritual Ibadah dan Pembinaan Akhlak) - Muhammad Shaleh Assingkily; Mahmud Arif; Marhumah Marhumah; Khamim Zarkasih Putro (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This article examines the living Qur’an and hadith through programmatic activities in madrasah ibtidaiyah (MI). During this time, the study of living Qur’an and hadith is dominated by the area of social research, both within the scope of certain communities and the wider community. In fact, this study is important to be developed in educational institutions, as an effort to restore the “spirit” of Islamic education and to make the Al-Qur’an hadith “living text” in MI. For this reason, this study analyzes al-Qur’an hadith learning and and programmed activities at MI Nurul Ummah. The main data was obtained through interviews, observations and study of documents focused on routines, rituals, and moral guidance in MI. The focus of these activities, in terms of oral, aural, writing, and attitude aspects. Thus, fulfilling the four aspects of something is referred to as the effort to live the Qur’an and hadith.